A Comparative Analysis of ELT Curriculum Approaches: Traditional vs Digital Material Integration - Engelina Salainti; La Sunra; Syarifuddin Dollah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
ABSTRACT This study examines the comparative effectiveness of traditional and digital material integration within English Language Teaching (ELT) curriculum, focusing on their respective impacts on student engagement, language proficiency, and learner autonomy. Traditional ELT approaches, grounded in structured, teacher-led instruction using textbooks and printed resources, have provided stability and reliability in language learning. However, the advent of digital materials has introduced interactive, personalized learning experiences through multimedia and online platforms, enhancing flexibility and student engagement. Employing a mixed-methods approach, the research collected data via surveys and interviews from a sample of pre-intermediate English students to explore preferences, challenges, and perceived benefits of each approach. Findings indicate that while traditional materials excel in delivering organized content and structured practice, digital materials significantly boost engagement, autonomy, and real-world application of language skills. Notably, learners expressed a preference for a blended approach, where traditional resources provide foundational knowledge and digital tools supplement with interactive exercises and multimedia exposure. Despite the advantages, digital integration also presented challenges, such as technological access issues and potential cognitive overload. This study concludes that a balanced integration of both traditional and digital materials can address diverse learner needs, supporting structured language acquisition while promoting engagement and adaptability in dynamic educational contexts. The results offer practical insights and best practices for curriculum developers and educators aiming to enhance language learning outcomes by combining traditional and digital methods.